Efficacy and safety of biosimilar CT-P17 versus reference adalimumab in subjects with rheumatoid arthritis: 24-week results from a randomized study - Kay, Jonathan; Jaworski, Janusz; Wojciechowski, Rafal; Wiland, Piotr; Dudek, Anna; Krogulec, Marek; Jeka, Slawomir; Zielinska, Agnieszka; Trefler, Jakub; Bartnicka-Maslowska, Katarzyna; Krajewska-Wlodarczyk, Magdalena; Klimiuk, Piotr A.; et al. (Arthritis research & therapy, 2021)
To demonstrate equivalent efficacy of the proposed high-concentration (100 mg/ml), citrate-free adalimumab biosimilar CT-P17 to European Union-approved adalimumab (EU-adalimumab) in subjects with active rheumatoid arthritis (RA). This randomized, double-blind phase III study ( ClinicalTrials.gov , NCT03789292) randomized (1:1) subjects with active RA at 52 centers to receive CT-P17 or EU-adalimumab 40 mg subcutaneously every 2 weeks until week 52. Results to week 24 are reported here. The primary endpoint was 20% improvement by American College of Rheumatology criteria (ACR20) response rate at week 24. Equivalence was concluded if the corresponding confidence intervals (CIs) for the estimate of treatment difference were within predefined equivalence margins: - 15 to 15% (95% CI; European Medicines Agency assumption); - 12 to 15% (90% CI; Food and Drug Administration assumption). Additional efficacy, pharmacokinetic, usability, safety, and immunogenicity endpoints were evaluated. 648 subjects were randomized (324 CT-P17; 324 EU-adalimumab). The ACR20 response rate at week 24 was 82.7% (n = 268/324) in both groups (intention-to-treat population). The 95% CI (- 5.94 to 5.94) and 90% CI (- 4.98 to 4.98) were within predefined equivalence margins for both assumptions and equivalent efficacy was concluded. Additional endpoints and overall safety were comparable between groups. Mean trough serum concentrations of CT-P17 were slightly higher than those of EU-adalimumab. Immunogenicity was slightly lower numerically for the CT-P17 group than for the EU-adalimumab group. CT-P17 and EU-adalimumab have equivalent efficacy and comparable safety and immunogenicity in subjects with active RA. Overall safety of CT-P17 is consistent with the known safety profile of reference adalimumab. ClinicalTrials.gov, NCT03789292 . Registered 28 December 2018-retrospectively registered.